Le véhicule autonome comme objet médiatique, scientifique et social (VACOM) - Rapport final de recherche pour le compte de la DGITM - Thébert, Mariane; Lesteven, Gaële; Bordignon, Frédérique; Pasquier, Delphine Du (HAL (Le Centre pour la Communication Scientifique Directe), 2018)
The VACOM project originated from the DGITM’s Intelligent Transport Mission questioning public perceptions of autonomous vehicles. What expectations and uncertainties does public opinion formulate in this period coming before the first sales of autonomous vehicles? The methodological choice was to analyze how autonomous vehicles are represented and staged in the media. Discourses were collected in the so-called "mainstream" newspaper and Internet media, and on Twitter's so-called "social" media, between December 2017 and May 2018. A body composed of articles published in national newspapers between 2012 and 2018 has been added to the current body for a diachronic analysis. Papers presented at the last five editions of the Transportation Research Board annual conference constituted a fourth body. The objective of this collection is to bring quantitative and qualitative knowledge regarding the way autonomous vehicles are treated in the media: how much information is disseminated on this subject via these channels? Who is behind this information? What problematic frameworks are the most frequently found?The report first discusses theoretical and methodological options. The second and third parts of the report present the main findings related to the analysis of the press body and of the Twitter body. The fourth part puts the two communication areas into perspective and considers the processes of production-diffusion-consumption of information.